A COMPARATIVE STUDY OF COPYRIGHT DISPUTE RESOLUTION THROUGH ARBITRATION BETWEEN INDONESIA AND THE UNITED KINGDOM - Ali Abdulah; Ade Maman Suherman; Tri Setiady; Wiwin Triyunarti (Justisi: Jurnal Ilmu Hukum, 2026)
Settling copyright disputes through arbitration is an out-of-court alternative that is considered more efficient, faster, and maintains the confidentiality of the parties' business. Indonesia, through Law No. 28 of 2014 concerning Copyright and Law No. 30 of 1999 concerning Arbitration, has opened up space for non-litigation copyright dispute resolution. Meanwhile, the United Kingdom with its common law system has developed a more mature arbitration mechanism through the Arbitration Act 1996 and the Copyright, Designs and Patents Act 1988. This article aims to comparatively analyze the arbitration system in resolving copyright disputes in Indonesia and the United Kingdom. The research method used is normative legal research with a statutory, conceptual, and comparative approach. The results of the study indicate that although both countries recognize arbitration as a dispute resolution forum, the United Kingdom has a more advanced legal infrastructure, international arbitration institutions, and practices than Indonesia. This study recommends strengthening copyright arbitration in Indonesia by adopting best practices from the UK, particularly regarding the specialization of IP arbitrators and the effectiveness of the enforcement of arbitral awards.